GENDER REVIEWED MATHEMATICAL INTUITION AT 7th GRADE STUDENTS THROUGH OPEN-ENDED BASED-INQUIRY LEARNING - Yuni, Yatha; Darhim, Darhim; Turmudi, Turmudi (Journal on Mathematics Education)
This study aims to examine the differences in studentsâ mathematical intuition abilities. Differences were reviewed by gender, through Open-ended Inquiry-Based Learning. The design of this study was a Pretest-Posttest Control Group Experiment. The subject of this study was 156 seventh graders of Madrasah Tsanawiyah in Bekasi, 77 male, and 79 female students. Data were analyzed with the help of SPSS. The result of this study showed p-value > ? (0,174 < 0,05). That means there was not different in mathematical intuition ability of male and female students.